Síntesis, identificación y estudio térmico de algunos nuevos polímeros inorgánicos basados en ligandos de bisditiocarbamato con silicona, teluro y algunos metales de transición - Nasir, H M; Saki, T.A; Al-Luaibi, M Y (Innovaciencia, 2019)
Introduction: In recent years, there has been considerable interest in dithiocarbamate complexes because of its diverse biological roles, very few reports have been made on polymeric bis- dithiocarbamate compounds with carbon chain of n-propyl or hexamethelene with transition metals in addition of the absence of any report of organosilicone or tellurium halides with such compounds Our interest in this report based on the preparation of new series of polymers with an expected activity as a fungi side compounds followed by the using of prepared amino compound as a hardners for epoxy paints Materials and Methods: A new polymers of the general structures –(MS2CNH(CH2)6NHCS2M-)n where [M= Cu, Cd, Mn and Zn] and –(M(R)2S2CNH(CH2)nNHCS2MR2-)m where [M= Si,R=CH 3 , n= 2 ,3 and 6 ; M=Te , R= Br , n= 2 ,3 and 6 ; M=Co, Ni R=Cl ; n= 6] have been prepared by reaction of MX2 where M= Ni ,Co, Cd , Mnor Zn , X= Cl ; M=Cu , X= SO4 , and dimethyl dichloro silane, tellurium tetrabromide with the corresponding sodium salts of bis-dithiocarbamateligands. Results and Discussion: Dimethyldichloro silane is a very sensitive material to O-H group, in addition to that, TeBr4 decomposed rapidlyin water so, a series solvents may be useful with such sensitive chemicals to water , in the other hand, dithiocarbamate ligands which is usually prepared in aqueous and alcoholic solution , must be prepared and isolated carefully to apply the other steps of synthesis using a chloroform solution as a solvent. It seems for the first view for dithiocarbamato ligands it may act as a bi dentate ligands using two sulphur donating atoms that is clearly appeared in common complexes such as diethyl dithiocarbamato or pipyridyl, morpholino dithiocarbamato with representation metal elements, even in such type of elements a sulfur bridges may formed. In this study, it showed clearly that Zinc and Cadimium polymers are diamagnetic polymers that is mean that these polymers are with oxidation state equal to (II) and a tetrahedral configuration Conclusions: The study showed that the new silicone polymers act as a stable polymers compared with others. All new polymers are of a high stability with large values of char contain with commercial epoxy. Among silicone polymers, the polymerwith carbon chain equal to 3 is more stable than that with 2 carbon atoms while the silicone polymer with 6 carbon atoms is the less stable one, may thermal treatment caused decomposition combined.